Neonatal febrile seizures: Dimethyl itaconate’s role in behavioral recovery and glutathione enzyme modulation in adult rats - Zohreh Ghotbeddin; Mohammad Abiri Jahromi; Ali Shahriari; Mohsen Peysokhan; Anahita Memar Dezfouli (PLoS ONE, 2025)
Febrile seizures are common in children and can lead to neurological deficits like motor impairments, memory problems, and cognitive decline. Research on dimethyl itaconate aims to mitigate these effects and improve the quality of life for affected people. By exploring its potential as a protective agent against oxidative stress during seizures, this study in adult male rats measures the activity of key enzymes related to oxidative stress and behavioral performance. Pregnant rats were divided into control, sham, DMI, febrile seizure, and DMI +  febrile seizure groups. Seizure severity was evaluated through threshold and frequency measurements, while memory, motor function, and balance were assessed using shuttle box, rotarod, open field, and wire hanging tests. After that, the hippocampus tissue was removed from the brain and the levels of MDA, SOD, GSH, TAC, GR, GPx, and catalase were measured through biochemical methods. Results show that dimethyl itaconate raised the seizure threshold and reduced tonic-clonic seizures. The DMI +  febrile seizure group also showed improved memory, movement, and balance compared to the febrile seizure group (p < 0.05 in all cases). Overall, dimethyl itaconate decreased oxidative stress and improved neurological outcomes in fever-affected rats.